Impact of Parental Attitude on Students’ Motivation to Learn Mathematics - Olopade, Isaac Adesola; Laka, Emmanuel Erintunde; Matilukuro, Oluwakore Muyideen (ALSYSTECH Journal of Education Technology, 2026)
This study investigates the impact of parental attitude on students’ motivation to learn mathematics, focusing on the mediating role of parental involvement and the moderating effects of socioeconomic status (SES) and school context. Using a descriptive correlational design, data were collected from 400 parent–student pairs in public and private secondary schools in the Ogbomoso Education Zone, Oyo State, Nigeria. The Parental Mathematics Attitude Scale (PMAS), Parental Involvement Index (PII), and Mathematics Motivation Inventory (MMI) were administered, and the data were analyzed using correlation, multiple regression, and mediation–moderation analysis. The results reveal a significant positive relationship between parental attitude and students’ motivation to learn mathematics (r = 0.61, p < 0.01), with parental attitude and parental involvement jointly explaining 46% of the variance in students’ motivation. Mediation analysis confirms that parental involvement partially mediates the relationship between parental attitude and students’ motivation, while SES and school context moderate this relationship, with stronger effects observed among urban and higher-SES families. The study concludes that fostering positive parental beliefs about mathematics and increasing parents’ active participation in their children’s mathematics learning can enhance students’ motivation, self-efficacy, and task value. It underscores the importance of parental workshops and strengthened school–home collaboration to promote supportive mathematics learning environments in Nigeria.